Modelagem da mortalidade por COVID-19 nos países europeus - Amaral, Leonardo de Salles (Universidade Federal de São Carlos, 2025)
The present study on modeling COVID-19 mortality in European countries provides insights into how each European nation behaved throughout the pandemic. The objective of this study is to model mortality using parametric GAMLSS models, as these models allow the response variable to belong to distributions beyond the exponential family, enabling a wide range of modeling options with various distributions. Due to the scale of the damage caused by COVID-19 globally, this study aims to identify variables that can explain the differences in mortality rates among European countries. Considering the sensitivity of the subject, it is crucial to pay attention to variables that, even with an apparently modest relationship, can have a significant impact on the response variable, as variations of only 0.1% in the covariates may reflect in thousands of lives affected. The results of this study can help health organizations and governments take the necessary measures to combat and manage future pandemics.
Modeling COVID-19 mortality in european countries
Keywords: COVID-19 pandemic; Parametric GAMLSS models; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO